Conceptualizing the State of the Art of Corporate Social Responsibility (CSR) in Green Construction and Its Nexus to Sustainable Development - Avotra, Andrianarivo Andriandafiarisoa Ralison Ny; Chenyun, Ye; Yongmin, Wu; Lijuan, Zhang; Nawaz, Ahsan (Frontiers in Environmental Science, 2021)
The study has been investigated on conceptualizing the state of the art of Cooperate Social Responsibility The study has been investigated on conceptualizing the state of the art of Cooperate Social Responsibility (CSR) in green construction and its nexus to Sustainable development. The research objective is to find out the significant relationship between CSR and green construction and further link green construction with sustainable development. The data has been collected from the 319 respondents working on different projects in the construction industry of china. The study is quantitative by nature. SEM analysis with the help of Smart-PLS has been applied to test the hypothesis relationship and mediations between components of CSR, green construction, and sustainable development. Results define that green procurement as a component of green construction strongly mediates between corporate social responsibility and sustainable development, green design and CO2 emission moderately mediates between corporate social responsibility and sustainable development. This research would add values, benefits, and knowledge towards reducing environmental temperature with the help of green construction occupying the effects of CSR on it. It would be helpful to change the trends in construction industry to make environmental health protective and to boost the sustainable development.